The Role and Efforts of the School Committee in Improving the Quality of Education at SMA Negeri 5 Banda Aceh - Ismail, Ismail; Shella Nathasya, Putri Norizan; Hadiyani, Rahmilia; Mustofa, Achmad; Anggraini, Irma; Ruaida, Ruaida (Universitas Syiah Kuala, 2023)
This research aims to determine (1) the role and efforts of the school committee in improving the quality of education at SMA Negeri 5 Banda Aceh and (2) the obstacles faced by the school committee in improving the quality of education at SMA Negeri 5 Banda Aceh. This article uses qualitative approach with qualitative descriptive research methods. The research subjects consisted of school principals and school committees. This research data collection technique is to use interview techniques, and documentation. The results of this study indicate that the school committee has carried out its role well, namely as an advisory agency, a supporter (supporting agency), a controller (controlling agency), and as a liaison agency (mediator agency). There are several obstacles faced by the school committee, namely in the implementation of learning carried out in schools is still limited to learning in the classroom, which means that learning is carried out limited to the delivery of material and the work plan has not been formed by the committee at SMA Negeri 5 Banda Aceh.